Di Balik Ketergantungan Zimbabwe terhadap Investasi Tiongkok Pasca Nasionalisasi Yuan sebagai Mata Uang Zimbabwe - Reza Aulia Rakhman (Jurnal Sentris, 2020)
On December 22nd 2015, President Zimbabwe Robert Mugabe officially declared that Zimbabwe will nationalize Yuan as official national currency. This policy is being done in order to solve default against Zimbabwe's debt to China. In return, China will pay off Zimbabwe's debt. By having this policy, foreign direct investment (FDI) as a foreign aid given by China will impact the economy development of Zimbabwe. This paper will examine Zimbabwe’s interdependence to China’s investment after nationalize Yuan as Zimbabwe’s currency with Theory of Foreign Capital Dependence and Development: A New Direction by Jeffrey Kentor and Terry Boswell